1999
DOI: 10.1002/(sici)1521-3773(19990115)38:1/2<179::aid-anie179>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

New Diphosphite Ligands for Catalytic Asymmetric Hydrogenation: The Crucial Role of Conformationally Enantiomeric Diols

Abstract: Efficient catalysis of asymmetric hydrogenations is possible with complexes of the type 1 which contain chiral diphosphites as ligands. Thus the Rh‐catalyzed hydrogenation of dimethyl itaconate with a catalyst containing 1,4:3,6‐dianhydro‐D‐mannite and conformationally enantiomeric diols is highly enantioselective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…14,15 Phosphoramidite F, which contains the atropisomeric bisphenol moiety, 29 reported by Alexakis, 30 gives even higher enantioselectivities for almost all products, leading to 77% for 4c. For 4b 71% ee is obtained, whereas only moderate ees have been reported until now for this substrate.…”
Section: Resultsmentioning
confidence: 97%
“…14,15 Phosphoramidite F, which contains the atropisomeric bisphenol moiety, 29 reported by Alexakis, 30 gives even higher enantioselectivities for almost all products, leading to 77% for 4c. For 4b 71% ee is obtained, whereas only moderate ees have been reported until now for this substrate.…”
Section: Resultsmentioning
confidence: 97%
“…See ref for bidentate phosphites having a chiral backbone and their use in rhodium-catalyzed hydrogenation of dimethyl itaconate. The stereochemistry of the product is determined by the stereochemistry of the P/O unit.…”
Section: Referencesmentioning
confidence: 99%
“…In conclusion, the synthesis of the common reactive intermediate pseudo-ortho-bis(dichlorophosphino)paracy- clophane (4) and the ready availability of the bisaryloxy building blocks has allowed the generation of a new class of phosphonites based on the paracyclophane backbone. Two ligands bearing the biphenoxy unit and the chiral binaphthoxy unit were identified as useful ligands for asymmetric hydrogenation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Reetz has recently reported that asymmetric alkene hydrogenation with biphenyl-based bisphosphite ligands displays an analogous difference between ligand diastereomers. 11 Our results obtained using diastereomeric structures of 2 indicate that achiral transformations mediated by bisphosphites are likewise effected by ligand structure.…”
mentioning
confidence: 79%